2019
DOI: 10.1002/cssc.201901076
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electrocatalytic CO2Reduction Driven by Ionic Liquid Buffer‐Like Solutions

Abstract: Electrocatalysis of CO2 reduction in aqueous electrolytes containing the ionic liquid (IL) 1‐n‐butyl‐2,3‐dimethylimidazolium acetate ([BMMIm][OAc]) and DMSO proceeded at low overpotentials (−0.9 V vs. Ag/AgCl) at commercially‐available Au electrodes, with high selectivity for CO production (58 % faradaic efficiency at −1.6 V vs. Ag/AgCl). 0.43 mol CO2 per mol IL could be absorbed into the electrolyte at atmospheric pressure, forming bicarbonate and providing a constant supply of dissolved CO2 to the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“… 62 Au 0.1 mol dm −3 [Bmim]OAc l /dimethyl sulfoxide/0.2 vol % H 2 O −1.80 V versus Ag/AgCl 8.6 CO 98 Gonçalves et al. 63 Pt 50 mM H[NTF 2 ] m /[Emim]NTF 2 HCOO − Martindale et al. 51 Post-transition Metal Catalysts Bi 20 mM [Emim]BF 4 /acetonitrile/0.1 M TBAPF 6 −1.95 V versus SCE n 5.51 ± 1.2 CO 95 ± 6 DiMeglio et al.…”
Section: Main Textmentioning
confidence: 99%
“… 62 Au 0.1 mol dm −3 [Bmim]OAc l /dimethyl sulfoxide/0.2 vol % H 2 O −1.80 V versus Ag/AgCl 8.6 CO 98 Gonçalves et al. 63 Pt 50 mM H[NTF 2 ] m /[Emim]NTF 2 HCOO − Martindale et al. 51 Post-transition Metal Catalysts Bi 20 mM [Emim]BF 4 /acetonitrile/0.1 M TBAPF 6 −1.95 V versus SCE n 5.51 ± 1.2 CO 95 ± 6 DiMeglio et al.…”
Section: Main Textmentioning
confidence: 99%
“…[38] The activation of CO 2 in these cases is probably caused by the breaking of the CO 2 linearity geometry, and in electroreductions, it is also assumed to be attributable to the stabilization of the CO 2 radical anion (CO 2 C À ) provided by the cation (usually imidazolium). [15,29,39] In some cases, the formation of bicarbonate/carbonate has been claimed as a result of the interaction of wet ILs containing phosphonium and ammonium cations associated with basic anions such as carboxylates or amino acids. [40,41] However, in most of these cases, it is claimed that basic (and even super-basic) anions perform a nucleophilic attack on CO 2 .…”
Section: Co 2 In Basic Ilsmentioning
confidence: 99%
“…Moreover, in various cases, the interaction of the IL pair changes the reactivity of the trapped water, which can easily react with substrates, products, and even with the IL. [8,9,19,[27][28][29][30] In this contribution, the different modes of interaction of CO 2 with bare ILs containing both nonbasic and mainly basic anions will be presented and discussed critically, considering recent examples reported in the literature. Finally, it will be demonstrated that simple concepts of acid-base chemistry can be used to explain and to design new ionic fluids for CO capture and activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was leveraged by Rosen et al, who used a room-temperature ionic liquid (RTIL) promoter for CO 2 reduction at silver cathodes. Since then, several other researchers have studied the use of RTILs to promote the reduction of coordinated nitrosyls or CO 2 . In particular, the efficient catalysis of CO 2 to CO was reported using a bismuth film electrode and ionic liquids, ,, and similar catalysis was carried out in acetonitrile/imidazolium-based electrolyte mixtures using thin CuSn films . In addition to promoting the reduction of small molecules, RTILs can also be used to direct the dominant reaction pathway for certain molecule activation processes. , While ionic interactions can accelerate the catalytic pathways, the use of protic ionic liquids (PIL) allows the promoter to facilitate both charge neutralization and provide the protons needed for a PCET reaction.…”
Section: Introductionmentioning
confidence: 99%